Introduction. Fragments of Order and Disorder in the Middle Ages (Doctor Virtualis, 2024)
This issue of "Doctor Virtualis" questions the concept of order and its value within medieval reflection: are we dealing with a cognitive instrument with which intellectuals of various training and operating in different fields try to deal with the complexity of their world, or, as one might at first sight expect from an period such as the Middle Ages, with a metaphysical structure already given, of an objective type, which represents a guarantee against the disharmony of the world and relations between men? The research hypothesis from which this issue originates is that even in the Middle Ages order presents itself as a need and therefore as the result of a construction that, through the most varied cognitive instruments, aims to account for disorder, attempting to unravel and dissolve the interweaving of causes and effects that characterises the various spaces of the world inhabited by men. For this reason, we have decided to title the issue Fragments of Order and Disorder in the Middle Ages.
Keywords: Order; Disorder; Middle Ages